Can automated alerts within computerized physician order entry improve compliance with laboratory practice guidelines for ordering Pap tests? - Lydia Pleotis Howell; Scott MacDonald; Jacqueline Jones; Daniel J Tancredi; Joy Melnikow (Elsevier, 2014)
Background: The electronic health record (EHR) provides opportunity to improve health and enhance appropriate test utilization through decision support. Electronic alerts in the order entry system can guide test use. Few published reports have assessed the impact of automated alerts on compliance of Pap ordering with published screening guidelines. Methods: Programming rules for Pap test ordering were developed within the EHR (Epic, Madison, WI) of the University of California, Davis Health System using American College of Obstetrics and Gynecology's 2009 guidelines and implemented in primary care clinics in 2010. Alerts discouraged Pap orders in women <21 and >71 years and displayed when an order was initiated. Providers were not prevented from placing an order. Results were measured during four calendar periods: (1) pre-alert (baseline) (July 2010 to June 2011), (2) post alert (alerts on) (July 2011 to December 2011), (3) inadvertent alert turn-off ("glitch") (January 2012 to December 2012), (5) post-glitch (alerts re-instated) (1/2013-7/2013). Metrics used to measure alert impact were between time and period seasonally adjusted relative frequency ratios. Results: Alerts were most effective in the <21 year old age group. During the baseline period 2.7 Pap tests were order in patients less than age 21 for every 100 Paps in those 21-71 years of age. This relative frequency decreased to 1.7 in the post-alert period and 1.4 during the glitch, with an even greater decline to 0.8 post-glitch when alerts were reinstated. Less impact was observed in the >70 year old group where the baseline relative frequency was 2.4 and declined to 2.1 post-alert, remained stable at 2.0 during the glitch period, and declined again to 1.7 post-glitch when alerts were reinstated. This likely reflects inclusion of women with a history of abnormal Pap tests for whom continued Pap testing is indicated, as well as reluctance by providers and patients to accept discontinuation of Pap testing for women with a history of normal Pap results. In both age groups, decreases in ordering were greatest when the alerts were functioning, indicating that the alerts had an effect beyond the influences of the environment. Conclusions: Discouraging alerts can impact ordering of Pap tests and improve compliance with established guidelines, thus avoiding unnecessary follow-up tests that can create potential patient harm and unnecessary expense. Alerts represent a potential model to address utilization of other lab tests. Longer study intervals are necessary to determine if provider compliance is maintained.